Wall shear stress angle determines aortic growth in patients with bicuspid aortic valves. (13th July 2021) - Minderhoud, SCS; Roos-Hesselink, JW; Chelu, RG; Bons, LR; Van Den Hoven, AT; Korteland, SA; Van Den Bosch, AE; Budde, RPJ; Wentzel, JJ; Hirsch, A
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): The Dutch Heart Foundation Background: Patients with bicuspid aortic valve (BAV) have altered flow velocity patterns with different wall shear stress (WSS) distributions in the ascending aorta compared to patients with tricuspid aortic valves. These WSS distributions are associated with aortic dilatation in cross sectional studies, however, longitudinal data demonstrating a potential causative role is missing. Purpose: The aim of this study was to assess the differences in WSS distributions between BAV patients and healthy subjects and to determine the predictive value of WSS for aortic growth in patients with a BAV. Methods: Forty patients with a BAV and 32 healthy matched subjects were prospectively studied by 4D-flow cardiovascular magnetic resonance (CMR). Peak velocity, pulse wave velocity, aortic distensibility, peak systolic WSS (magnitude), the different WSS components (axial and circumferential), and WSS angle were assessed in the proximal ascending aorta. WSS angle was defined as the angle between the WSSmagnitude and WSSaxial component. In the BAV patients, aortic volumetric growth over three years was determined in the proximal ascending aorta (first 5cm) based on CT angiography. Multivariate linear regression analysis was used to identify independent predictors of aortic volumetric growth. Results: Of the BAV patients, 21 (53%) had a left-right fusion pattern and eight patients had Turner syndrome. WSSaxial was significantly lower in BAV patients compared to healthy subjects (p = 0.008) and WSScircumferential and WSS angle were significantly higher (both p < 0.001, see Figure). WSSmagnitude, pulse wave velocity, and aorta distensibility were not statistically significant different. WSSmagnitude (0.69 N/m² [0.51-0.81] vs 1.08 N/m² [0.89-1.24], p = 0.005), WSSaxial (0.50 N/m² [0.39-0.61] vs 0.72 N/m²  [0.54-0.94], p = 0.015) and WSScircumferential (0.34 N/m² [0.32-0.46] vs 0.64 N/m² [0.47-0.81], p = 0.008) were significantly lower in BAV Turner patients compared to BAV non-Turner patients, while WSS angle (40° [34-41] vs 40° [32-48], p = 0.607) was not statistically significant different. During a follow-up of three years, there was a significant growth of the proximal ascending aorta in the BAV patients (1.2 cm3 [-0.2-2.5], p = 0.001). In multivariate analysis corrected for baseline aortic volume and diastolic blood pressure, WSS angle was the only independent predictor for proximal aortic volume growth (β=0.108, p = 0.030). Conclusions: Increased WSScircumferential and especially WSS angle are present in patients with BAV. WSS angle was the only independent predictor of aortic growth. These findings highlight the potential role of  WSS measurements in patients with BAV to stratify patients at risk for aortic dilation.